Flight control system synthesis using eigenstructure assignment - Shapiro, E. Y.; Chung, J. C. (Journal of optimization theory and applications, 1984)
The central topic of this paper is the establishment of an efficient practical synthesis procedure for modern flight control systems. Unlike the classical design methodology (Bode plots, Nichols plot, etc.) and optimal control techniques, the present approach provides the designer a direct approach for the synthesis of desired control laws. Although the setting is the now familiar state space, the actual design is performed relative to classical specifications (i.e., modes and mode distribution) by placing closed-loop engenvalues and eigenvectors at some desired locations (regions) within the state space. The new method can handle output feedback configurations, subject to controller structural constraints. Complete theoretical background an a realistic numerical example are provided.